Factors influencing migration of Metapenaeus dobsoni (Miers, 1878) in the Negombo Lagoon - Jayawardane, P A A T; Gunawardane, M G K (Indian Journal of Fisheries, 2011)
The factors influencing migration of M. dobsoni in the Negombo lagoon, Sri Lanka are presented. Juveniles of M. dobsoni occur in the Negombo lagoon and on maturing they return to the sea off Negombo for reproduction. The cohort analysis indicated two pulses of immigration to the nursery areas in February and June. The estimated growth rates for juveniles were relatively high compared to that of adults. Three groups of shrimps were identified in the lagoon : small quick movers, larger long stay ones and an intermediate group. Emigration is not restricted to maturing juveniles but occurs across all the ages. There were few identifiable emigration pulses from lagoon towards the off shore areas. It appears that the resultant osmotic stress due to low saline waters in the lagoon during the periods with high precipitation levels may be the strongest influence triggering the onset of emigration of shrimps.